Finely Tuned Blue Iridium Complexes with Varying Horizontal Emission Dipole Ratios and Quantum Yields for Phosphorescent Organic Light‐Emitting Diodes. Issue 2 (22nd October 2014) - Lee, Jeong‐Hwan; Sarada, Ganguri; Moon, Chang‐Ki; Cho, Woosum; Kim, Kwon‐Hyeon; Park, Young Geun; Lee, Jin Yong; Jin, Sung‐Ho; Kim, Jang‐Joo
<x xml:space="preserve">Abstract</x> Two new heteroleptic blue emitting Ir(III) complexes, EtOCN‐FIracac and tBuCN‐FIracac, and a homoleptic Ir(III) complex, tBu‐FCNIr, consisting of 2′, 4″‐difluorophenylpyridine (dfppy) with a cyano (CN) group at the 5′ position of the phenyl and an ethoxy (EtO‐) or tert‐butyl (tBu) group at the 4 position of the pyridine as the main ligands, are synthesized and characterized for phosphorescent organic light‐emitting diodes (PhOLEDs). The dual functionalization of the dfppy core with the electron‐withdrawing CN and electron‐donating EtO‐ or tBu‐ groups leads to improved blue color purity by compensating the bathochromic shift originating from the ancillary ligand of the heteroleptic Ir(III) complex and contributes to the enhancement of the horizontal ratio of emitting dipoles (Θ), which is one of the promising approaches to improve the efficiency of PhOLEDs. PhOLEDs based on tBuCN‐FIracac and EtOCN‐FIracac show one of the highest efficiencies ever achieved for blue color, with maximum external quantum efficiencies (EQEs) of 22.3% (39.2 cd A−1) and 21.5% (35.1 cd A−1), respectively, with a simple device structure; a similar device based on tBu‐FCNIr displays a maximum EQE of 16.2% (23.5 cd A−1). The performance of PhOLEDs based on the two heteroleptic Ir(III) complexes are highly improved compared to tBu‐FCNIr, due to the increased θ and photoluminescence quantum yield (PLQY).